Metformin Pharmacology and Drug Interactions - Akhtar, Juber; Ahmad, Usama; Irfan Khan, Mohammad (IntechOpen, 2021)
Type 2 diabetes (T2D), also known as non-insulin-dependent diabetes mellitus (NIDDM), is a condition in which cells fail to respond to insulin properly. As the disease progresses, the body does not produce enough insulin. There are several classes of anti-diabetic medications available, including the oral agent metformin. This medication is recommended as first-line treatment for T2D, except for those patients with severe kidney or liver problems. This book discusses the molecular mechanism, pharmacokinetics, and uses of metformin, as well as presents information on adverse drug reactions, drug interactions, and the potential use of metformin in tuberculosis.